2020
DOI: 10.1002/dys.1672
|View full text |Cite
|
Sign up to set email alerts
|

Profile of language abilities in a sample of adults with developmental disorders

Abstract: This study investigated the profile of language abilities in a sample of high‐achieving English speaking adults with developmental disorders. Ninety‐seven adult participants were recruited: 49 with a dyslexia diagnosis (dyslexic group), 16 with a diagnosis of a different developmental disorder including dyspraxia, autism and SpLD (non‐dyslexic developmental disorder group) and 32 with no diagnosis (non‐disordered group). Dyslexic and non‐dyslexic developmental disorder groups demonstrated similar impairments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…For example, significant problems regarding the speed of articulatory movements involved in speech production have been found in participants aged 6-11 years [84], 9-14 years [85], and 13-16 years [86]. Similar results were reported by Bradshaw, Woodhead, Thompson, and Snowling [87], who used a sentence repetition task from the NEPSY [88] to evaluate deficits in oro-motor skills in adults with dyslexia. Moreover, Griffiths and Frith [89] used an articulatory awareness task in which adults with dyslexia had to repeat orally presented phonemes and match them with schematic drawings of their articulations.…”
Section: The Relationship Between Phonemic and Motor Deficits In Adul...supporting
confidence: 73%
See 1 more Smart Citation
“…For example, significant problems regarding the speed of articulatory movements involved in speech production have been found in participants aged 6-11 years [84], 9-14 years [85], and 13-16 years [86]. Similar results were reported by Bradshaw, Woodhead, Thompson, and Snowling [87], who used a sentence repetition task from the NEPSY [88] to evaluate deficits in oro-motor skills in adults with dyslexia. Moreover, Griffiths and Frith [89] used an articulatory awareness task in which adults with dyslexia had to repeat orally presented phonemes and match them with schematic drawings of their articulations.…”
Section: The Relationship Between Phonemic and Motor Deficits In Adul...supporting
confidence: 73%
“…In DDK tasks, participants are asked to repeat meaningless syllables (e.g., a single syllable /puh/, /kuh/, and /tuh/ or a syllable sequence /puh-kuh-tuh/ or /pa-ta-ka/), produced by combining vowels and consonants, for a period of time and under time pressure. According to studies conducted with adults [87][88][89], articulatory deficits in a DDK task are expected in both adult groups with dyslexia, with the impairment being exacerbated in the comorbid group.…”
Section: The Present Studymentioning
confidence: 99%
“…It would be interesting to investigate whether children who receive a formal diagnosis of dyslexia or a SCD fall within this category when children are classified using the cluster analysis approach described in this research. Previous research found that group membership derived through clustering was not a good predictor of diagnostic labels (Astle et al, 2019; Bradshaw et al, 2021). However, these studies used different clustering procedures than those used in this research and included a more diverse range of learning difficulties.…”
Section: Discussionmentioning
confidence: 93%
“…Since Orton's pioneering research on dyslexia, there has been a growing body of research on the genetic and neurocognitive origins and profiles of dyslexia in both child and adult populations. In comparison to non‐dyslexic adults, AWD are likely to encounter challenges including reading proficiency, processing speed, executive functioning skills, working memory, prospective memory, and structural language skills (Bradshaw et al, 2021; Del Tufo & Earle, 2020; Leather et al, 2011; Smith‐Spark, 2018; Smith‐Spark et al, 2023; Wiseheart et al, 2009). While neurocognitive differences commence in childhood, they persist into adulthood, severely impacting individuals' experiences in key life domains, including postsecondary education and employment.…”
Section: Literature Reviewmentioning
confidence: 99%